Green aldose isomerisation: 2-C-methyl-1,4-lactones from the reaction of Amadori ketoses with calcium hydroxide - Hotchkiss, D; Soengas, R; Booth, K; Weymouth-Wilson, A; Eastwick-Field, V; Fleet, G (2007)
Saccharinic acids, branched 2-C-methyl-aldonic acids, may be accessed via a green procedure from aldoses by sequential conversion to an Amadori ketose and treatment with calcium hydroxide; d-galactose and d-glucose are converted to 2-C-methyl-d-lyxono-1,4-lactone (with a small amount of 2-C-methyl-d-xylono-1,4-lactone) and 2-C-methyl-d-ribono-1,4-lactone. Inversion of configuration at C-4 of the branched lactones allows access to 2-C-methyl-l-ribono-1,4-lactone and 2-C-methyl-l-lyxono-1,4-lactone, respectively. d-Xylose affords 2-C-methyl-d-threono-1,4-lactone and 2-C-methyl-d-erythrono-1,4-lactone, whereas l-arabinose, under similar conditions, gave the enantiomers 2-C-methyl-l-threono-1,4-lactone and 2-C-methyl-l-erythrono-1,4-lactone. © 2006.